Credibilidade das políticas monetária e fiscal e risco país : uma análise empírica para o caso brasileiro - Demura, Kiara de Deus (2018)
This paper is aimed at analyzing the effect of monetary and fiscal credibility on country risk in the case of a large emerging economy. Brazil is one of the largest emerging economies today, with the presence of public and private assets in the financial market. While Brazilian economic agents seek financing in the market, investors observe the behavior of these agents and the functioning of the economy to evaluate the risk of application in these assets. Given that country risk indicates the instability of the economy and that credibility reflects the ability to anchor the expectations of agents on the outcome of economic policies, it is expected that increasing the credibility of monetary and fiscal policies will reduce the risk as uncertainty about the future of the economy. Thus, this paper observes how credibility gains can result in risk reduction and shows how sovereign risk interferes in the country risk assessment, then shows that is possible to analyze the risk of the economy from the sovereign risk. It uses indexes available in the literature to measure monetary and fiscal credibility in Brazil between 2003 and 2016 and, subsequently, empirically verify the effect of monetary and fiscal credibility on Brazil risk. The results of the estimates point to the gains of fiscal credibility as a means of reducing Brazil's economic instability. Although monetary credibility is not significant, there are indications that concern about inflation in Brazil still exists and raises the risk of default.